1999
DOI: 10.1364/ol.24.000948
|View full text |Cite
|
Sign up to set email alerts
|

Use of two-photon excitation for erasable–rewritable three-dimensional bit optical data storage in a photorefractive polymer

Abstract: We report what is believed to be the first use of a photorefractive polymer in erasable-rewritable three-dimensional bit optical data storage under two-photon excitation. We successfully demonstrate writing, erasing, and rewriting of multilayered information in a photorefractive polymer consisting of 2,5-dimethyl-4-(p-nitrophenylazo)anisole, 2,4,7-trinitro-9-fluorenone, 9-ethylcarbazole, and poly(N-vinylcarbazole). A three-dimensional bit density of 5 Gbits/cm(3) is achieved by two-photon absorption under puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 9 publications
0
70
0
Order By: Relevance
“…50 3D, three-dimensional; 5D, five-dimensional; HDD, hard disk drive; ODS, optical data storage; PB, petabyte; SPIN, super-resolution photoinductioninhibition nanolithography. encrypted in the two polarization states of writing beams at 0 6 -and 45 6 oriented polarizations through polarization-induced birefringence. 24 Recently, it has been demonstrated that by employing the depolarization effect through the tight focusing of a radially polarized beam, one can generate a longitudinal polarization state within the focal region.…”
Section: Ultrahigh Securitymentioning
confidence: 99%
“…50 3D, three-dimensional; 5D, five-dimensional; HDD, hard disk drive; ODS, optical data storage; PB, petabyte; SPIN, super-resolution photoinductioninhibition nanolithography. encrypted in the two polarization states of writing beams at 0 6 -and 45 6 oriented polarizations through polarization-induced birefringence. 24 Recently, it has been demonstrated that by employing the depolarization effect through the tight focusing of a radially polarized beam, one can generate a longitudinal polarization state within the focal region.…”
Section: Ultrahigh Securitymentioning
confidence: 99%
“…4 it is clear to see that in the investigated spectral range the QRs show a superior 2P sensitivity compared to QDs of similar diameters. Especially in the window of 800-960 nm, which has been widely applied in 2P fluorescence bioimaging, 21 threedimensional optical data storage, 22 and microfabrication, 23 the 2P absorption cross section of QR is one to two orders of magnitude larger than that of QDs.…”
Section: ͑4͒mentioning
confidence: 99%
“…3͒ has been widely applied in a variety of materials for 3D optical data storage. [1][2][3][4][5][6][7][8][9][10][11] In particular, the use of photochromic materials has attracted intensive interest owning to the capability of picosecond response and rewritability. [3][4][5][6][7] Similarly, quantum dots ͑QDs͒ have been incorporated into photochromic system as fluorescence resonance energy transfer ͑FRET͒ donors 11,12 under single photon excitation due to their amazing optical properties such as the sizedependent broad tunability of absorption and emission bands.…”
Section: Two-photon Energy Transfer Enhanced Three-dimensional Opticamentioning
confidence: 99%